LITHUANIAN MUSEUM GOVERNANCE: A PATHWAY TOWARD THE MODERN MUSEUM - Bortkevičiūtė, Rasa (Politologija, 2017)
There is a broad consensus that public institutions must constantly change in order to provide high quality services and meet the needs of the public. However, population surveys and researchers in this field claim that Lithuanian museum governance is exclusive, with traditional forms of management still being dominant. Modern museum management theory emerged to contrast this kind of management. It is based on New Public Governance (further – NPG) principles and can be explained using four main ideas – the refusal of the hierarchical model of management; an orientation toward visitors and their inclusion in the museum’s activities; cross-sectoral cooperation; transparency and accountability. This work provides an overview of how NPG tools are linked with modern museum governance; further discussed are their applications and main causes, which affect their usage in Lithuanian museums. The research consists of three main parts. In the first part, the Lithuanian judicial system and policies, related with the museums sector, were analyzed. Research revealed a lack of solid Lithuanian museum policy. The main Lithuanian Republic Museums Law is compulsory for all institutions, but it is old-fashioned and represents traditional forms of governance. On the other hand, the newest sector documents reflect the main NPG ideas, but their role is more of a consulting one, mandatory to fulfill only for a certain category of museums. With no strong judicial basis for their actions, the governance of museums highly depends on the ideas of certain museum authorities. The second part – quantitative research – was carried out according to the previously mentioned four ideas of modern museum governance. It was revealed that museums have made attempts to apply horizontal management inside the institutions but have still excluded external actors. So, even if this cooperation exists, it takes place in a formal exchange of information rather than the common creation of content. While most of the museum’s activity data is open to the public, quantitative indicators do not reveal the quality of performance, and most museums do not tend to evaluate their results critically. Overall, the research results clearly stated that the practice of Lithuanian museum governance is still in the middle on the path toward the modern museum. In the third part, the main reasons that affect the usage of NPG tools in Lithuanian museums were analyzed by using the qualitative research method. We saw that the most important museum governance problem is the non-functional incentives and sanction mechanisms (the funding does not correlate with the performance of a museum) as well as a lack of a solid, national-level museum policy. The given circumstances provide a lot of decision-making freedom for heads of museums and allow them to set the main principles of a particular museum’s governance, which usually leads to the strengthening of traditional management. To conclude, the research revealed that the theoretical model of reinvented museum governance is still not fully implemented in Lithuanian museums. It also allows an offering of practical recommendations for the further spread of NPG tools. Regarding internal museum governance, institutions should become more open and inclusive – constructive opinions of museum personnel, as well as open possibilities for co-operation with external actors, should be taken into account. The most important issues for the museum sector would be the creation of an unanimous museum policy, an inclusion of museum officials into the process of national-level policy creation and implementation as well as, finally, the establishment of a new financing mechanism for museums that would directly link a museum’s performance to the funding it receives.